Profile of special needs patients assisted in a dental project - Faker, Khawana; Di Lanaro, Nattalia; Paula, Viviane Andrade Cancio; Tostes, Mônica Almeida (Brazilian Dental Science, 2016)
Objective: The aim of this paper was to outline the profile of patients with special needs who sought treatment at School of Dentistry, Universidade Federal Fluminense (FO-UFF). Material and Methods: We evaluated the charts of 17 patients who sought care during the survey period. The variables were gender, age, reason for consultation, continuous use of psychotropic drugs, socioeconomic status, consumption of sugar, toothbrushing frequency, dental occlusion dental care and length of treatment. All patients were treated by two undergraduate students linked to the project under supervision. Results: The mean age of the patients was 9.65 years old and males were the most prevalent (52.94%). Individuals with mental retardation and Down´s syndrome were the predominant group seeking dental care (35,3%) and pain was cited as the main reason (58,82%). The average dmft 0.9 (±1,4) and DMFT was 3.29 (±7,07) among patients and restorative treatment was provided for 25% of the patients. Conclusions: In conclusion the greatest demand was for curative and not preventive procedures and that the prevalence of caries is high in this group of patients.Keywords: Dental caries; DMFT index; Intellectual disability.